A bibliometric analysis of the social return on investment - Begoña Gutiérrez-Nieto; Juan Camón-Cala; Beatriz Cuéllar-Fernández; Yolanda Fuertes-Callén (Humanities & Social Sciences Communications)
Abstract This paper presents a thorough bibliometric analysis of the Social Return on Investment (SROI), an innovative method for measuring social impact. Using data from the Web of Science and the VOSviewer tool, we offer a comprehensive overview of the research evolution on SROI, analyzing it from citation, co-occurrence, and co-citation perspectives. The number of publications for the research topic has notably risen in recent years, and we delve into the evolution of research lines. The analyses disclose trends in SROI research, offering insights for researchers to comprehend the current state of the art of the field.